Efforts to Improve Elementary School Students’ Learning Outcomes in Islamic Religious Education through the Implementation of a Cooperative Learning Model - Arnilawati Arnilawati (Southeast Asian Journal of Global Trends and Issues in Education, 2026)
Background: Students’ low learning outcomes in Islamic Religious Education are often associated with limited variation in instructional models and the continued dominance of conventional, teacher-centred approaches. Such conditions tend to reduce student engagement, limit interaction, and hinder the development of critical understanding. Objective: This study aims to improve students’ learning outcomes by implementing a cooperative learning model among fourth-grade students at SD Negeri 75 Palembang. Method: The research employed Classroom Action Research (CAR) conducted in three cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through classroom observations and learning outcome tests, and analysis used a descriptive, quantitative approach to measure improvement across cycles. Results: The findings reveal a significant improvement in students’ learning outcomes, demonstrated by the consistent increase in average scores and the percentage of mastery learning from the pre-cycle to cycle III. Student participation and engagement also showed noticeable enhancement during the learning process. Conclusion: The cooperative learning model is effective in improving both academic achievement and student activeness. Contribution: This study provides practical insights for teachers to adopt innovative instructional strategies to improve learning quality.